Validity of Mangled Extremity Score System to Predict Limb Salvage on Cases of Traumatic Popliteal Artery Injuries: A Case Series and Review of the Literature - Abdelghaffar Hanfy Mahmoud, Amr; AbdelSamie Khalek Elbahat , Mohamed (Journal of Endovascular Resuscitation and Trauma Management, 2023)
Background: Popliteal artery injuries carry a risk of amputation rate ranging from 9.7% to 28%. The mangled extremity score system (MESS) was originally authenticated in only 26 patients and it was concluded that an MESS ≥ 7 equated to a 100% rate of amputation. In this study we add the effects of combined arterial venous injuries and combined arterial venous and nerve injuries to the risk of amputation and correlate them with the MESS. Methods: This is a retrospective single arm cohort study conducted using 25 patients included between 1 January 2020 and 1 January 2023 at two hospitals, Ain Shams University Hospital and Shebin Elkoom Teaching Hospital. The study defined two groups: the amputation and non-amputation groups. It assessed the validity of the MESS to predict limb salvage in cases of traumatic popliteal artery injuries. Results: The overall rate of amputation was 64%. Patients presenting with MESS ≥ 8 had an amputation rate of 25%, while patients with MESS ≥ 9 had an amputation rate of 75%. Patients presenting with combined popliteal artery and vein or combined artery, vein and nerve injury had a 100% rate of amputation (MESS ≥ 8). There was no 30-day mortality. Conclusions: MESS ≥ 9 carries a high risk of amputation (75%). Combined arterial and venous injuries or arterial, venous and nerve injuries, which already have a high MESS, also carry a high risk of amputation. All of them could be predictors of limb salvage in popliteal artery injury.